Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.20945/2359-3997000000178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of overweight and obesity on pregnancy outcomes in women with gestational diabetes – results from a retrospective multicenter study

Abstract: Objective: The aim of this study was to evaluate the impact of pre-pregnancy body mass index (BMI) on pregnancy outcomes in women with gestational diabetes (GD). Subjects and methods: Retrospective multicenter study using data from the Portuguese National Register. We included women with GD with a singleton pregnancy. GD diagnosis was according to the International Association of the Diabetes and Pregnancy Study Group criteria. Women were divided into groups according to their pre-pregnancy BMI: < 18.5 kg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
3
7
0
2
Order By: Relevance
“…Moreover, the finding in our study on association between underweight and LBW was also in line with previous literature (Li et al, 2013;Liu et al, 2012). Previous literature has revealed that maternal overweight and obesity were associated with the increased risk for gestational hypertension and caesarian delivery (Lewandowska, Wieckowska & Sajdak, 2020;Machado, Monteiro & Oliveira, 2020;Vince et al, 2020). Our study also confirmed these findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the finding in our study on association between underweight and LBW was also in line with previous literature (Li et al, 2013;Liu et al, 2012). Previous literature has revealed that maternal overweight and obesity were associated with the increased risk for gestational hypertension and caesarian delivery (Lewandowska, Wieckowska & Sajdak, 2020;Machado, Monteiro & Oliveira, 2020;Vince et al, 2020). Our study also confirmed these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Previous literature has revealed that maternal overweight and obesity were associated with the increased risk for gestational hypertension and caesarian delivery ( Lewandowska, Wieckowska & Sajdak, 2020 ; Machado, Monteiro & Oliveira, 2020 ; Vince et al, 2020 ). Our study also confirmed these findings.…”
Section: Discussionmentioning
confidence: 99%
“…the prevalence of overweight and inactivity and dietary changes (4)(5)(6). In the HAPO study, blood glucose levels in the 75-g OGTT before and 1 and 2 h after glucose intake were independently associated with maternal and perinatal complications (2).…”
mentioning
confidence: 99%
“…Pesquisas nacionais e internacionais com DMG, identificaram excesso de peso em período pré-gestacional, com variação de 47,8% a 74% (Guerra et al, 2018;Larrabure-Torrealva et al, 2018;Machado et al, 2019;Tavares et al, 2019).…”
Section: Resultsunclassified
“…Em relação ao ganho ponderal excessivo, a literatura mostra variação de 26,1% a 35,4%, com maiores valores em mulheres com sobrepeso e obesidade pré-gestacional (36,7% e 36,9%) respectivamente. Ao mesmo tempo que gestantes de baixo peso (48,3%) e eutróficas (50,2%), podem apresentar ganho ponderal abaixo do recomendado (Machado et al, 2019;Tavares et al, 2019). Ademais foi observada associação estatística significante entre o ganho ponderal e o estado nutricional prévio no estudo de Machado et al (2019); fato não observado no presente estudo.…”
Section: Resultsunclassified